Disseminated actinomycosis in an immunocompetent patient: A case report - Sandoval-Mallma, Erick (2019)
This case report describes a 58-year-old patient who visited the hospital after an 8-month disease period characterized by multiple skin and soft tissue abscesses associated with an approximately 20-kg weight loss, severe hypoalbuminemia, moderate anemia and polyserositis. Several imaging tests revealed abscesses on the left thigh muscle. Additionally, abdomen, pelvis and thorax ultrasounds showed bilateral interstitial nephropathy, ascites and bilateral pleural effusion. The histopathological examination confirmed the diagnosis of actinomycosis. Given the systemic manifestations and diffuse distribution of the abscesses, the case was clinically consistent with disseminated actinomycosis. Therefore, the patient received IV antibiotic treatment with penicillin G sodium for 4 weeks and then with amoxicillin p.o. The patient evolved favorably and exhibited abscess remission.